Hemimandibulectomy and intermaxillary fixation: surgical treatment of ameloblastoma in mandible: a case report - Sandiah, Jihad H.; Priyanto, Winarno; Adiantoro, Seto; Nurwiadh, Agus (Hasanuddin University, 2019)
Objective: Ameloblastoma is a tumor derived from epithelial, gingival mucosa or gingivomaxillary that appear on a teeth. It is a benign yet destructive tumor with high recurrence rate. Hemimandibulectomy is one of therapies selected when the pathologic lesion had involved the coronoid processus and the condyle, although the therapy could results in facial defects and mandibular deviation.The purpose of this article is to report a hemimandibulectomy with bridging plate reconstruction and inter-maxillary fixation as a therapy for left mandibular ameloblastoma performed to reduce deviation and facial defects.Method: Fourty-two years old female patient came to the Oral and Maxillofacial Surgery Clinic at Hasan Sadikin Hospital Bandung, with a lump at the left side of lower jaw, it happened since 3 years ago, with small size in the beginning and grow gradually, painless, hard on palpation, and same colored with surrounding tissue.Result: The histopathologic examination results was plexiform type ameloblastoma at left mandible. Hemimandibulectomy is the removal of most or half of the mandible including the entire condyloideus process, coronoid processus, ramus and some mandibular corpus on one side of the jaw. Ameloblastoma is the most common odontogenic tumor in the mandible and maxilla. Ameloblastoma has several variations of histopathologic appearance, but the most commonly seen is the follicular and plexiform type. In most cases, ameloblastoma is usually asymptomatic, growing slowly, and can expand in the affected jaw.Conclusion: Hemimandibulectomy performed to remove pathologic lesions radically to prevent recurrence. Bridging plate is an act used as a mandibular reconstruction. Intermaxillary fixation is one of the ways to reduce mandibular deviation after hemimandibulectomy.Keywords: hemimandibulectomy, intermaxillary fixation, ameloblastoma